Investigation of the pulsed breakdown mechanism at the surface of a dielectric in a vacuum-II: Nonuniform field; Soviet Physics: Technical Physics; Vol. 12 - Bugaev S. P. (1968, 1968)
В фонде НТБ ТПУ отсутствует